Effects of Pgam1-mediated glycolysis pathway in Sertoli cells on Spermatogonial stem cells based on transcriptomics and energy metabolomics - An, Xuejiao; Li, Qiao; Chen, Nana; Li, Taotao; Wang, Huihui; Su, Manchun; Shi, Huibin; Ma, Youji (Frontiers in Veterinary Science, 2022)
Spermatogenesis is a complex process involving a variety of intercellular interactions and precise regulation of gene expression. Spermatogenesis is sustained by a foundational Spermatogonial stem cells (SSCs) and in mammalian testis. Sertoli cells (SCs) are the major component of SSC niche. Sertoli cells provide structural support and supply energy substrate for developing germ cells. Phosphoglycerate mutase 1 (Pgam1) is a key enzyme in the glycolytic metabolism and our previous work showed that Pgam1 is expressed in SCs. In the present study, hypothesized that Pgam1-depedent glycolysis in SCs plays a functional role in regulating SSCs fate decisions. A co-culture system of murine SCs and primary spermatogonia was constructed to investigate the effects of Pgam1 knockdown or overexpression on SSCs proliferation and differentiation. Transcriptome results indicated that overexpression and knockdown of Pgam1 in SCs resulted in up-regulation of 458 genes (117 down-regulated, 341 up-regulated) and down-regulation of 409 genes (110 down-regulated, 299 up-regulated), respectively. Further analysis of these DEGs revealed that GDNF, FGF2 and other genes that serve key roles in SSCs niche maintenance were regulated by Pgam1. The metabolome results showed that a total of 11 and 16 differential metabolites were identified in the Pgam1 gene overexpression and knockdown respectively. Further screening of these metabolites indicated that Sertoli cell derived glutamate, glutamine, threonine, leucine, alanine, lysine, serine, succinate, fumarate, phosphoenolpyruvate, ATP, ADP and AMP have potential roles in regulating SSCs proliferation and differentiation. In summary, this study established a SCs-SSCs co-culture system and identified a list of genes and small metabolic molecules that affect the proliferation and differentiation of SSCs. This study provides additional insights into the regulatory mechanisms underlying interactions between SCs and SSCs during mammalian spermatogenesis.